Benign esophageal strictures: about 13 operated cases - Praderi, Luis A (Cirugía del Uruguay, 2020)
A survey is carried out of a personal series of 13 cases of benign esophageal stenosis comprising, 8 diaphragmatic herniations, 1 cardiofundic malformation, 2 aclasias and 1 inferior esophageal membrane .. In 39 cases of hiatal herniations, 7 presented stenosis; in the reversible forms, only Nissen's funduplicature was used, with excellent results, due consideration being given to backflow upon ga,stric herniation. The irreversible forms were treated with cardioplasty of the HeinekeMiculicz type followed by Thal's apposition or funduplicature. Nissen's method is regarded as satisfactory for cardiofundic malformations and stenoses following failule of other procedures, such as Allison's. In cases of acalasia the Heller-Kole methods is advocated, but with angle repain in order to prevent the consequent backflow syndrome. The case of esophageal membrane is dealt with in detail, the writeh advising endoscopy at surgery in order to plot its height, followed by esophagotomy.